An Exhaustive Survey on Security Solutions in MANETS - Kalambe, KB; Apte, SM (International Journal of Computer Sciences and Engineering, 2025)
Wireless ad-hoc network is a self arranged wireless network comprised of large number of self controlled sensor nodes or mobile nodes. These self controlled nodes are randomly distributed in a decentralized network. These nodes connect with others node using the connectionless links. They have no information about location of other nodes. They are communicating with each other by sensing the position of every other node. They can sense within some specific transmission range. They possess the non uniform structure. Because of their non uniform structure and decentralized nature, wireless network may prone to various attacks so secure routing in wireless network is a critical task. It may consist of some trusted node or it may contain some malicious node, so it is difficult to detect whether the packet is forward to trusted or malicious nodes. So for this kind of problem several security techniques have been proposed. But a full proof protocol is yet to be discovered to handle all the attacks in an integrated manner and therefore still it is a challenge for new researchers. In this survey paper, various existing security protocol have been discussed in details. This Paper is a survey about what are the various types of attacks can occur in routing Protocol and how the security technique is followed in a particular protocol.